William A. Gamson and His Legacy for Academia and Social Movements. Issue 2 (1st December 2021) - Gawerc, Michelle I.; Meyer, David S.
Abstract: William A. Gamson's career was nothing less than remarkable. A prolific scholar, Gamson wrote at least eight books and more than a hundred articles from 1961 to 2014. And he bequeathed social movement studies substantial theoretical contributions and methodological innovations in numerous areas including coalitions, resource mobilization, political opportunities, framing, and culture. His legacy also includes pioneering simulation games both for teaching and for use by social movements, novel pedagogies (in part inspired by his wife, sociologist, Zelda Gamson), and a well-articulated scholar-activist model that has—and will continue—to inspire. This article discusses his extraordinary career and his legacy for social movements, academia, and beyond.